Organised crime targeting elderly people: a theoretical overview : in the framework of the project ‘The development of the observatory function of the European Centre of Expertise on Crime Prevention within the EUCPN’ -EUCPN Secretariat, February 2015, Brussels - Colaes, Sinke (Theoretical paper, 2017)
This theoretical paper is published by the EUCPN Secretariat in connection with the theme of the Slovakian Presidency, which was organised crime targeting elderly people. The growing population of elderly in the EU can be seen for many criminals as an opportunity to create new markets. Therefore, firstly, this paper looks up close to the utility of crime prevention working with a specific target group. Secondly, there is an attempt to give a definition of the heterogeneous group of elderly. Additionally, it is important to provide an overview of crimes which can be used to target elderly victims. Not only an overview of the variation of crimes, also an overview of the modus operandi of the offenders, will be provided in order to give a helping hand to practitioners.